2013
DOI: 10.1016/j.yjmcc.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in expression and biophysics of ion channels in the canine ventricle

Abstract: Background Developmental changes in the electrical characteristics of the ventricular myocardium are not well defined. This study examines the contribution of inwardly rectifying K+ current (IK1), transient outward K+ current (Ito), delayed rectifier K+ currents (IKr and IKs) and sodium channel current (INa) to repolarization in the canine neonate myocardium. Methods Single myocytes isolated from the left ventricle of 2-3 week old canine neonate hearts were studied using patch-clamp techniques. Results Neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…We measured the expression of major ion channel and cardiac genes in each of the three culture conditions compared to the routine medium condition. We noted significant upregulation of genes encoding for the major cardiac potassium channel subunits associated with the fatty acid and T 3 treatment: KCND3 and KCNQ1 expression, which are known to be more pronounced in canine adult (as compared to neonatal) ventricular tissue ( 25 ), were increased 7.1- and 1.5-fold, respectively. KCNJ2 , which encodes for the pore of the inward rectifier K + channel ( 26 ), a key regulator of phase 3 and known to be upregulated in cardiac development ( 27 ), increased 4.9-fold.…”
Section: Resultsmentioning
confidence: 83%
“…We measured the expression of major ion channel and cardiac genes in each of the three culture conditions compared to the routine medium condition. We noted significant upregulation of genes encoding for the major cardiac potassium channel subunits associated with the fatty acid and T 3 treatment: KCND3 and KCNQ1 expression, which are known to be more pronounced in canine adult (as compared to neonatal) ventricular tissue ( 25 ), were increased 7.1- and 1.5-fold, respectively. KCNJ2 , which encodes for the pore of the inward rectifier K + channel ( 26 ), a key regulator of phase 3 and known to be upregulated in cardiac development ( 27 ), increased 4.9-fold.…”
Section: Resultsmentioning
confidence: 83%
“…Several key properties governing EpC and conduction overall are known to change during development: Cells in neonatal myocardium do not have fully formed IDs, and Na + channels and GJs are distributed diffusively throughout the sarcolemma (Fromaget et al, 1992;Vreeker et al, 2014). Consistent with reduced Na + channel expression, it has been shown that pediatric cardiomyocytes produce a reduced I Na , compared to adult cardiomyocytes (Cai et al, 2011;Cordeiro et al, 2013). Cx43 is essentially undetectable until 23 weeks in utero and remain randomly distributed on the sarcolemma in neonatal cardiomyocytes (Peters et al, 1994;Hirschy et al, 2006;Vreeker et al, 2014;Swift et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Na v 1.5channels, however, reside on the lateral membrane in neonatal cardiomyocytes and begin to begin to preferentially localize at the ID around 5 months postnatal, much earlier than Cx43 (Harrell et al, 2007 ; Vreeker et al, 2014 ). Additionally, studies have shown that adult cardiomyocytes are larger than neonatal cardiomyocytes (Cordeiro et al, 2013 ; Vreeker et al, 2014 ; Swift et al, 2020 ). This is especially important given that cell size broadly influences all electrical activity in the cell by altering surface area, cell volume, membrane capacitance, ion channel expression, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the canine ventricle, four K + currents play important roles in controlling the cardiac action potential duration 15 : (i) a Ca 2+ -independent transient outward K + current ( I to1 ) (in contrast to the Ca 2+ -dependent current, I to2 6 ); (ii) a rapid and slow delayed rectifier K + current ( I Kr and I Ks , respectively) and (iii) an inwardly rectifying K + current ( I K1 ). I K1 has been identified in the myocardium of most mammalian species (for review see 7, 8 ), but the density of I K1 among different species as well as among different cardiac tissue types is highly variable 911 .…”
Section: Introductionmentioning
confidence: 99%